Multidimensional Analysis of Sustainability and Integration of Sustainable Energy Practices in Petroleum Field Management - Ariyon, Muhammad; Sukendi, Sukendi; Putra, Ridwan Manda; Kausarian, Husnul (International Journal of Energy Economics and Policy, 2024)
This study illustrates the importance of sustainable energy management in the context of oil field management in Indonesia. Using the Rappetro approach, this research evaluates the sustainability of oil field management across various dimensions, including ecological, economic, socio-cultural, technological, and legal-institutional aspects. Findings indicate that the sustainability index for all dimensions—ecology (64.07%), economy (57.72%), socio-cultural (52.91%), technology (64.44%), and legal-institutional (61.7%)—is robust. This signifies that oil exploration and exploitation operations in the area have effectively integrated conservation principles. Energy management and balanced integration of ecological, economic, and technological aspects in oil field management play a key role in ensuring long-term sustainability. Theoretically, this research provides valuable insights for the energy sector by highlighting the sustainability of oil field management. Its implications are relevant in shaping sustainable energy practices, emphasizing the need for a comprehensive approach in every stage of oil resource exploration and exploitation. Thus, this study makes a significant contribution to guiding policies and practices that support sustainable energy development in the future.